2009
DOI: 10.1007/s12257-008-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonication assistance increases the efficiency of isoflavones extraction from kudzu (Pueraria lobata Ohwi) roots waste

Abstract: ^Äëíê~Åí= This study assesses the use of ultrasonication to improve the extraction process of classical solvent extraction methods for extracting isoflavones from the kudzu roots waste. The kudzu roots waste was produced after squeezing fresh kudzu roots to make juice. The effects of extraction time, extraction temperature, ultrasonic power, and ethanol concentration in ethanol/water mixtures were investigated. The extraction yield was found to increase with extraction time and temperature. The application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Currently, in the field of biotechnology, sonoporation has a broad range of applications, including its use for inhibition of food-borne pathogens in processed food (Forghani et al, 2013;Koolman et al, 2014), disruption of various kinds of cells (Ren et al, 2007;Sudar et al, 2013;Zhou et al, 2014), and assistance in bioactive component extraction (Kwun et al, 2009;Liu et al, 2011). The present study demonstrated that sonoporation can immediately and effectively homogenize liquid-cultured mycelial pellets of G. lucidum, and highly uniform mycelia can be obtained.…”
Section: Discussionmentioning
confidence: 53%
“…Currently, in the field of biotechnology, sonoporation has a broad range of applications, including its use for inhibition of food-borne pathogens in processed food (Forghani et al, 2013;Koolman et al, 2014), disruption of various kinds of cells (Ren et al, 2007;Sudar et al, 2013;Zhou et al, 2014), and assistance in bioactive component extraction (Kwun et al, 2009;Liu et al, 2011). The present study demonstrated that sonoporation can immediately and effectively homogenize liquid-cultured mycelial pellets of G. lucidum, and highly uniform mycelia can be obtained.…”
Section: Discussionmentioning
confidence: 53%
“…The peaks appearing at 3435.16 cm −1 reveal the presence of −OH groups. 8 Indeed, the facile and stable deposition of pyrolyzed biochar over cotton fabric exhibits a black porous and diffused texture, which facilitates the trapping of incident light as well as excellent hydrophilicity validated by dynamic contact angle investigations for effective water transport.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, biomass can be regarded as a carbon-neutral source of energy because it can capture almost as much CO 2 during photosynthesis as is released when it is burned. 7,8 However, the research community developed controlled and sustainable techniques, e.g., pyrolysis, for the decomposition of invasive species into useful products as carbon sequestration agents. The pyrolysis approach is cost-effective and environmentfriendly for the carbonization of biomass to fulfill the requirement of sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of literature is available reporting on the clinical and pre-clinical studies undertaken that have demonstrated these phytochemicals to impart various health benefits, such as anti-cancer, anti-diabetic, antiallergic, anti-hyperglycemia, and cholesterol-lowering effects (Duru et al, 2018;Takasugi et al, 2014;Valachovicova et al, 2004). Apart from the aforementioned plant sources, isoflavones can also be found in soy molasses, a low-value by-product generated during the production of soy protein concentrate (Kwun et al, 2009;Prasain et al, 2003;Yang et al, 2018). Generally, soy molasses and parts of kudzu (roots, stems and flowers) are regarded as a waste/by-product in the manufacturing process (Vacek et al, 2008).…”
Section: Introductionmentioning
confidence: 99%